UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MINAT BELAJAR SISWA - Lilis Sunariah; Umi Kulsum; Mujiyatun (UNISAN JURNAL, 2023)
The purpose of descriptive research is to make systematically factual and accurate descriptions, drawings or drawings of the facts, characteristics and relationships between the phenomena being investigated. The results of this study are Islamic Religious Education Teachers at SMP PGRI 2 Katibung South Lampung have made various efforts to increase interest in learning, namely formulating clear and interesting learning objectives, showing enthusiasm in teaching, creating a pleasant atmosphere, involving students in the learning process, giving praise (prizes) to students' achievements, giving jobs and assignments, motivating students to study hard, showing learning results (evaluation), appreciating student work and giving criticism with a smile. Internal factors that influence the efforts of Islamic Religious Education teachers at SMP PGRI 2 Katibung South Lampung in increasing interest in learning are students' poor study habits, while external factors are the school environment which is less conducive.